Applying a Systems Perspective to Preventive Health: How Can It Be Useful?; Comment on "What Can Policy-Makers Get Out of Systems Thinking? Policy Partners' Experiences of a Systems-Focused Research Collaboration in Preventive Health" - Matt Egan; Elizabeth McGill (Kerman University of Medical Sciences, 2021)
Advocates suggest that a paradigm shift in preventive health towards systems thinking is desirable and may be underway. In a recent study of policy-makers' opinions, Haynes and colleagues found a mixed response to an Australian initiative that sought to apply systems theories and associated methods to preventive health. Some were enthusiastic about systems, but others were concerned or unconvinced about its usefulness. This commentary responds to such concerns. We argue that a systems perspective can help provide policy-makers with timely evidence to inform decisions about intervention planning and delivery. We also suggest that research applying a systems perspective could provide policy-makers with evidence to support planning and incremental decision-making; make recommendations to support intervention adaptability; consider potential barriers due to incoherent systems, and consider the political consequences of interventions.